2022
DOI: 10.4308/hjb.29.2.146-154
|View full text |Cite
|
Sign up to set email alerts
|

Role of Fe2+-dependent Reaction in Biodecolorization of Methyl Orange by Brown-rot Fungus Fomitopsis pinicola

Abstract: The involvement of Fenton reaction on biodegradation of methyl orange (MO) by brown-rot fungus Fomitopsis pinicola was investigated based on Fe2+-dependent reaction. The degradation of MO (final concentration 75 mg/L) was performed in mineral salt media with and without Fe2+ with incubation period at 0, 7, 14, 21, and 28 days. Degradation analysis was performed using UV-Vis Spectrophotometer and LC-TOF/MS. F. pinicola decolorized MO in a medium containing Fe2+ and a medium that lacked the mineral, at percentag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Several studies have shown that MO is subjected to both symmetric and asymmetric fragmentations, which are catalyzed by azoreductase and lignin peroxidase, respectively. 8,97 Furthermore, laccase is strongly included in thiazole yellow G's desulfonation and demethylation reactions. 98 This confirms that R. pickettii laccase is used in molecule A's desulfonation and demethylation reactions, resulting in the production of fragments B and C. Overall, the diverse enzymatic activities of different microbial strains play a crucial role in the fragmentation of MO.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have shown that MO is subjected to both symmetric and asymmetric fragmentations, which are catalyzed by azoreductase and lignin peroxidase, respectively. 8,97 Furthermore, laccase is strongly included in thiazole yellow G's desulfonation and demethylation reactions. 98 This confirms that R. pickettii laccase is used in molecule A's desulfonation and demethylation reactions, resulting in the production of fragments B and C. Overall, the diverse enzymatic activities of different microbial strains play a crucial role in the fragmentation of MO.…”
Section: Resultsmentioning
confidence: 99%
“…Pure hectorite showed an inferior degree of removal (3.93%; 0.783 mg g −1 ), because the naturally available sites were similar to those of the sulphate group (-SO 3 − ) in MO. 1,47 Based on the value of capacity and degree of removal, it shows that BHec-40 has the best performance and was selected for further adsorption experiments. pH, pH pzc and beads dose effect.…”
Section: Batch Sorption Studymentioning
confidence: 99%
“…Biodecolorization and biodegradation of MB were performed on MSM, prepared according to modified Kirk's medium [8], by dissolving 0. The mycelium culture of D. dickinsii was inoculated to MSM and supplemented with MB at its final concentration of 75 mg/L.…”
Section: Decolorization and Degradation Of Mb Using D Dickinsiimentioning
confidence: 99%
“…BRF produces hydrogen peroxide (H 2 O 2 ) and utilizes Fe 2+ from the media and substrate to carry out the Fenton reaction, leading to hydroxyl radical (•OH) production. These fungi were reported using hydroxyl radicals produced through the Fenton reaction (Fe 2+ + H 2 O 2 ) to degrade xenobiotic compounds [8]. Previous studies have shown that BRF species such as Gloeophyllum trabeum, Fomitopsis pinicola, and Daedalea dickinsii can degrade 1,1,1trichloro-2,2-bis(4-chlorophenyl) ethane (DDT) by the involvement of Fenton reaction [9].…”
Section: ■ Introductionmentioning
confidence: 99%